Oxidative Phosphorylation Is Dysregulated Within the Basocortical Circuit in a 6-month old Mouse Model of Down Syndrome and Alzheimer’s Disease - Alldred, Melissa J.; Lee, Sang Han; Stutzmann, Grace E.; Ginsberg, Stephen D. (Frontiers in Aging Neuroscience, 2021)
Down syndrome (DS) is the primary genetic cause of intellectual disability, which is due to the triplication of human chromosome 21 (HSA21). In addition to intellectual disability, HSA21 trisomy results in a number of neurological and physiological pathologies in individuals with DS, including progressive cognitive dysfunction and learning and memory deficits which worsen with age. Further exacerbating neurological dysfunction associated with DS is the concomitant basal forebrain cholinergic neuron (BFCN) degeneration and onset of Alzheimer’s disease (AD) pathology in early mid-life. We previously interrogated the underlying pathways of dysregulation within the BFCN system, utilizing laser capture microdissection, single population RNA sequencing (RNA-seq) analysis, and bioinformatic inquiry on cholinergic neurons within the medial septal nucleus/ventral diagonal band (MSN/VDB) in a DS/AD model, the Ts65Dn mouse, at a timepoint (6 months of age) commensurate with BFCN degeneration. Bioinformatic inquiry indicated the mitochondrial oxidative phosphorylation pathway was significantly impacted, with a select subset of genes downregulated. To address this translationally relevant pathway dysregulation, we queried genes and encoded proteins within brain regions comprising the basocortical system, a significant contributor to memory and executive function. We demonstrate in trisomic mice significant deficits in basal forebrain (BF) gene and encoded protein levels in multiple complexes within the mitochondrial oxidative phosphorylation pathway. We interrogated these genes and encoded proteins in frontal cortex (Fr Ctx) and found concomitant alterations in gene expression, but not at the protein level, suggesting that BF alterations precede or pace cortical dysfunction within the basocortical circuit. We propose the onset of severe dysregulation in oxidative phosphorylation complexes is an early marker of cognitive decline and specifically linked to BFCN degeneration that may propagate throughout cortical memory and executive function circuits in DS and AD.